Fading phenomena in li-rich layered oxide material for lithium-ion batteries - Kim, T (2015)
Lithium-rich layered transition metal oxide cathode, represented as the chemical formula of xLi2MnO3 · (1 - x)LiMO2(M = Mn, Ni, Co) , retains immense interest as one of the most promising candidates for energy storage system ranging from mobile devices to electric vehicle applications (EV/HEV/PHEV). This battery type benefits from superior theoretical capacity (>250 mAhg-1), high chemical potential (>4.6 V vs Li0), good thermal stability, high discharge capacity and lower cost compared with conventional cathodes (e.g. LiCoO2, Li(Ni1/3Mn1/3Co1/3)O2 cathodes). However, there remain major barriers which still need to be improved in order to achieve a successful commercialization for large-scale devices or electric vehicle applications. The irreversible capacity loss of 40-100 mAhg-1 during the initial electrochemical cycle and the battery fading phenomena (capacity fading/voltage decay) on further cycles are the major problems which have emerged. The Li+ ion extraction accompanied by oxygen release from the active material in the form of oxide known as lithia (Li2O) along with the transition metal migration has been suggested as the dominant processes underlying the capacity fading mechanism. Those processes, in turn, cause a phase transition from a layered structure into a spinel within the electrode material. The interplay of the local atomic environments between Li2MnO3 (monoclinic, C2/m) and LiMO2 (trigonal/hexagonal, R3m) holds the key to developing better cathodes with enhanced stability. In the present thesis, an in operando XAS study using a specially-designed cell of the graphene- coated Li(Li0.2Mn0.54Ni0.13Co0.13)O2 cathode is employed to examine the chemical, electronic, and structural states of the transition metals (Mn, Co, and Ni) during electrochemical cycle(s). Precise oxidation states for the transition metals is evaluated by the combined analyses from the XANES and SQUID measurements. The K-edge XANES spectral shift is quantified to investigate the contribution to the charge compensation mechanism by the oxidation change. Absorption features in K-edge XANES are identified. These features describe the electronic state of the individual atoms in the cathode composite, as well as the local distortion from the octahedral structure of MO6. The Fourier transform of EXAFS offers a satisfactory description of the local structure changes with the connection to the cation arrangement. The description is generally involved with the peak amplitude, position, shape changes (trend), and coordination numbers in the real space. Hence, similarities or discrepancies in the local atomic environments could be compared at different state of charge. Major structural parameters are deduced from the EXAFS fitting process. These parameters can be used to distinguish different atomic environments upon voltage bias levels or investigate the appearance of the Jahn-Teller effect. A new approach to understand the atomic environment upon charge-discharge is demonstrated, namely, a Continuous Cauchy Wavelet Transform (CCWT) which enables the visualization of the EXAFS spectra in three dimensions by decomposing the k-space and R-space (uncorrected for phase shift) signals. The wavelet transform analysis provides possible evidence of the precursor that leads to the spinel phase transition in this battery system.